Keberdayaan Ekonomi Kelompok Wanita Tani Melalui Pengembangan Usaha Agribisnis Pedesaan (PUAP), (Studi Kasus : Usaha Agribisnis Sayuran di Desa Pandan Wangi Kecamatan Peranap Kabupaten Indragiri Hulu) - Elisabeth Situmorang; Rosnita '; Novia Dewi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Recently, the Economic Performance of Women Group Farmer through Rural Agribusiness Development (PUAP) become an important issue in Indonesia. The objective of this study is to observe economic performance of the Women Group Farmer in Pandan Wangi Village. The method of survey was used in this research. Data was collected using purposive sampling based on criteria such as, active members in PUAP, Age of 15 to 64 years, more than six year business experience in agriculture. The study use Likert’s Summated Rating Scale(LSRS) to analyse participation of respondents. The results show that category of economic performance of the women group farmer is moderate with score 3.07. The use of capital has improved significantly the business performance, farmers’ income and their wellfare. Keywords:Performance,Women Farmer, PUAP, Economic Factors